Resettlement experiences and alternatives in Thailand - Thopa, Gopal B.; Weber, Karl E. (1988)
Problems concerning the resettlement of those made homeless by the construction of dams to create reservoirs in Thailand are considered. The authors attempt "firstly, to examine the rationale for spontaneous and planned resettlement in Thailand. Secondly, the determinants of the success or failure of resettlers are explored with reference to selected planned resettlement projects. Finally, resettlement alternatives for prospective reservoir evacuees are proposed."